Impact of Introducing Intensity Modulated Radiotherapy on Curative Intent Radiotherapy and Survival for Lung Cancer - Fornacon-Wood, Isabella; Chan, Clara; Bayman, Neil; Banfill, Kathryn; Coote, Joanna; Garbett, Alex; Harris, Margaret; Hudson, Andrew; Kennedy, Jason; Pemberton, Laura; Salem, Ahmed; Sheikh, Hamid; et al. (Frontiers in Oncology, 2022)
Background Lung cancer survival remains poor. The introduction of Intensity-Modulated Radiotherapy (IMRT) allows treatment of more complex tumours as it improves conformity around the tumour and greater normal tissue sparing. However, there is limited evidence assessing the clinical impact of IMRT. In this study, we evaluated whether the introduction of IMRT had an influence on the proportion of patients treated with curative-intent radiotherapy over time, and whether this had an effect on patient survival. Materials and Methods Patients treated with thoracic radiotherapy at our institute between 2005 and 2020 were retrospectively identified and grouped into three time periods: A) 2005-2008 (pre-IMRT), B) 2009-2012 (selective use of IMRT), and C) 2013-2020 (full access to IMRT). Data on performance status (PS), stage, age, gross tumour volume (GTV), planning target volume (PTV) and survival were collected. The proportion of patients treated with a curative dose between these periods was compared. Multivariable survival models were fitted to evaluate the hazard for patients treated in each time period, adjusting for PS, stage, age and tumour volume. Results 12,499 patients were included in the analysis (n=2675 (A), n=3127 (B), and n=6697 (C)). The proportion of patients treated with curative-intent radiotherapy increased between the 3 time periods, from 38.1% to 50.2% to 65.6% (p<0.001). When stage IV patients were excluded, this increased to 40.1% to 58.1% to 82.9% (p<0.001). This trend was seen across all PS and stages. The GTV size increased across the time periods and PTV size decreased. Patients treated with curative-intent during period C had a survival improvement compared to time period A when adjusting for clinical variables (HR=0.725 (0.632-0.831), p<0.001). Conclusion IMRT was associated with to more patients receiving curative-intent radiotherapy. In addition, it facilitated the treatment of larger tumours that historically would have been treated palliatively. Despite treating larger, more complex tumours with curative-intent, a survival benefit was seen for patients treated when full access to IMRT was available (2013-2020). This study highlights the impact of IMRT on thoracic oncology practice, accepting that improved survival may also be attributed to a number of other contributing factors, including improvements in staging, other technological radiotherapy advances and changes to systemic treatment.